Nephrological problems in a child with Aicardi-Goutières syndrome - Małgorzata Piejak; Zuzanna Hus; Adam Bujanowicz; Piotr Skrzypczyk; Joanna Samotyjek; Beata Jurkiewicz; Hanna Szymanik-Grzelak; Mariusz I. Furmanek; Małgorzata Pańczyk-Tomaszewska (Pediatria Polska)
Aicardi-Goutières syndrome (AGS) is a rare genetic disorder characterized by excessive interferon-alpha production, leading to central nervous system damage, manifesting as subacute encephalopathy in infancy. Moreover, the phenotype includes frostbite-like skin lesions, hepatosplenomegaly, and endocrinopathies. Here we report a case of a patient with this syndrome and a concurrent urinary system malformation. A 3-year-old boy with AGS was referred to the nephrology clinic due to recurrent urinary tract infections. Diagnostics including voiding cystourethrography and renal scintigraphy revealed left-sided grade III vesicoureteral reflux and minor post-inflammatory lesions. Subsequent cystometry indicated subvesical obstruction, and posterior urethral valves were incised during cystoscopy. Since the initiation of treatment with furazidine, doxazosin and oxybutynin hydrochloride, the urinary tract infection has not recurred. Urinary system anomalies are a common issue in genetic syndromes. To date, urinary tract abnormalities have not been described as a part of the AGS phenotype.